SmartDR: algorithms and techniques for fast detailed routing with good design rule handling - Gonçalves, Stephano Machado Moreira (2020)
Detailed routing is one of the most challenging and time-consuming steps of the design of integrated circuits. The routing solution must obey all of the design rules so that the circuit can be properly manufactured. However, design rule handling may be very challenging, regarding its algorithmic solutions and implementation, and may easily lead to unfeasible runtimes. In order to make the detailed routing resolution more feasible, it is divided into two steps, where in the first, called initial detailed routing, an almost complete solution is achieved by relaxing design rules. In the second step the remaining design rule violations are solved. However, the more these rules are left to be handled in the second stage, the greater is the chance that they will not be completely solved, and this usually occurs. Thus, it is necessary to face the challenge of dealing with as many rules as possible in the first step without compromising the runtime. Thus, this work proposes an initial detailed router, called SmartDR, to meet these needs, that is, to provide a good design rule handling while keeping a good runtime. The main features of the router that meet these goals are pin access and path search techniques. This work proposes a novel pin access method, in which the pin access paths share the same routing resources and are dynamically legalized and implemented. It is also proposed a new path search algorithm, based on A *-interval search, which is aware of several design rules. A new method to improve the A * heuristic function is also proposed, taking into account the peculiarities of detailed routing, which leads to a better runtime. Using ISPD 2018 Contest benchmarks, all proposed methods were evaluated separately and altogether in the proposed router, which was compared with state-of-the-art routers. The experiments show that the proposed techniques contribute to runtime and design rule handling improvement, as well as it demonstrates that SmartDR is superior to the state-of-the-art routers in these metrics.